Analisis Faktor-Faktor Yang Mempengaruhi Indeks Pembangunan Manusia Di Kabupaten Asahan 2016-2021 - Adrian, M. Fikri; Harahap, Muhammad Ikhsan (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
This study aims to determine the factors that affect the Human Development Index (HDI) in Asahan Regency. In this study using variables that are considered to affect the Human Development Index (HDI), namely : poverty and economic growth.Â  The Data obtained in the form of our time series was sourced from the Central Statistics Agency (BPS) of North Sumatra for the period 2016 â€“ 2021). The method used in this study is multiple Linear regression. The results of this study can be concluded that : poverty and economic growth simultaneously have a significant effect on the Human Development Index (HDI) in Asahan Regency; poverty has a negative and insignificant effect on the Human Development Index. This means that when the HDI value falls, poverty increases, and vice versa; economic growth has a negative and insignificant effect on the Human Development Index. This means that when economic growth increases, the value of HDI will decrease, and vice versa.